2010
DOI: 10.1071/mf10040
|View full text |Cite
|
Sign up to set email alerts
|

Life-history traits of the southern hemisphere eastern red scorpionfish, Scorpaena cardinalis (Scorpaenidae: Scorpaeninae)

Abstract: Abstract. Fishes of the family Scorpaenidae (scorpionfish/rockfish) are important to benthic rocky-reef communities and fisheries globally. The present study is the first to provide biological information for any species of the genus Scorpaena (Scorpaena cardinalis) in southern hemisphere waters, namely south-eastern Australia. Growth of S. cardinalis was estimated using size-at-age data from sectioned otoliths. Growth was slow, with fish attaining ,22 cm after 5 years and 26 cm after 10 years. The oldest fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…counted) on some individuals until late summer (February). This spring-summer timing of completion of opaque zone formation concurs with that observed for western populations of S. robusta and a range of other east Australian coastal and estuarine teleosts, including platycephalids (Barnes, Gray, & Williamson, 2011;Gray, Gale, Stringfellow, & Raines, 2002), scorpaenids (Stewart & Hughes, 2010), girellids (Gray, Ives, Macbeth, & Kendall, 2010;Stocks et al, 2014) and sparids (Gray, 2015;Hughes, Stewart, Kendall, & Gray, 2008).…”
Section: Age and Growthsupporting
confidence: 85%
“…counted) on some individuals until late summer (February). This spring-summer timing of completion of opaque zone formation concurs with that observed for western populations of S. robusta and a range of other east Australian coastal and estuarine teleosts, including platycephalids (Barnes, Gray, & Williamson, 2011;Gray, Gale, Stringfellow, & Raines, 2002), scorpaenids (Stewart & Hughes, 2010), girellids (Gray, Ives, Macbeth, & Kendall, 2010;Stocks et al, 2014) and sparids (Gray, 2015;Hughes, Stewart, Kendall, & Gray, 2008).…”
Section: Age and Growthsupporting
confidence: 85%
“…Biological information on S. jacksoniensis (as S. cardinalis) was reported by Stewart and Hughes (2010), who estimated the oldest individual to be 33 years old. They also found that the spawning peak in New South Wales waters was March, and the species had a highly specialized ovary adapted for the production of a floating gelatinous egg mass.…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about the impact of artisanal fishing on rockfish populations. Stewart and Hughes (2010) and Mason (1998) revealed the long history of depletion that many species of the family Scorpaenidae have suffered, with population resilience declining due to the removal of larger and older fish (Leaman and Beamish, 1984). Moreover, the negative anthropogenic impact on the reproductive potential of scorpaenids caused by pollution has been demonstrated for S. porcus (Oven et al, 2000).…”
Section: Rockfish Are Valuable Target Species For Artisanal Fisheriesmentioning
confidence: 99%